Espaços lusófonos: uma abordagem entre Brasil e Portugal - Moreno, Sandra Retamiro (2008)
Speaking a language is the necessary condition of an individual that belongs to a society, of a certain nation. This subject concerns the autonomy of the people, in their identity and self-determination, as well as to the establishment and the maintenance of social relationships. Taking that into account, this study will analyze two journalistic speeches of different spaces (Brazil and Portugal) in written media, considering the same theme (education). The study was made under the perspective of the analysis of the speech (AD), of French orientation, to establish the similarities and the existent differences of these speeches in the journalistic discursive modality, turning possible, therefore, to think about the scenography built in the speech and increasing the construction of the speech of the linguistic marks of the discursive formation and of the ideological formation.